2000
DOI: 10.2134/jeq2000.00472425002900010001x
|View full text |Cite
|
Sign up to set email alerts
|

Practical and Innovative Measures for the Control of Agricultural Phosphorus Losses to Water: An Overview

Abstract: Inputs of P are essential for profitable crop and livestock production. However, its export in watershed runoff can accelerate the eutrophication of receiving fresh waters. The specialization of crop and livestock farming has created regional imbalances in P inputs in feed and fertilizer and output in farm produce. In many areas, soil P exceeds crop needs and has enriched surface runoff with P. This paper provides a brief overview of P management strategies to maintain agricultural production and protect water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
198
2
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(209 citation statements)
references
References 23 publications
2
198
2
4
Order By: Relevance
“…Some of the observed data of P concentration in runoff were over 0.1 mg/l, even 0.8 mg/l (Table 3). This meant, in the hilly area of loess plateau, current level of soil phosphorus could cause eutrophication of downstream water (Sharpley et al 2000). As the study site was in the subarea short of nitrogen and phosphorus (Jia et al 1994), controlling runoff from FR was helpful to abate the phosphorus pollution press of downstream water of Yellow river.…”
Section: Resultsmentioning
confidence: 98%
“…Some of the observed data of P concentration in runoff were over 0.1 mg/l, even 0.8 mg/l (Table 3). This meant, in the hilly area of loess plateau, current level of soil phosphorus could cause eutrophication of downstream water (Sharpley et al 2000). As the study site was in the subarea short of nitrogen and phosphorus (Jia et al 1994), controlling runoff from FR was helpful to abate the phosphorus pollution press of downstream water of Yellow river.…”
Section: Resultsmentioning
confidence: 98%
“…The mechanical composition, soil water characteristics, bulk density, and hydraulic conductivity are remarkably similar among different samples taken from different fields of the same type of soil (12, 13). We tested variations of the concentrations of exchangeable Na, K, Mg, and Ca, Bray-1 P, and total organic carbon (TOC) in the top 60 cm soils sampled from fields 5,6,8,9,17,18,28,29, and 34. We found that each type of soil also has very similar chemical properties, even though they may be sampled from different fields, which allows use of only a few samples to obtain the information with negligible error.…”
Section: Methodsmentioning
confidence: 99%
“…However, the use efficiency of applied P is generally very low, ranging from 10% to 30% in the year applied (McLaughlin et al 1991). Continuous application of P fertilisers also increases the risk of P loss from soil to water, causing toxic algal blooms in water bodies (Sharpley et al 2000). Improving plant uptake of P from soil is an obvious alternative to the management of low P soils and the enhancement of use efficiency of P fertilisers.…”
Section: Introductionmentioning
confidence: 99%